Application of a non-species dependent ELISA for the detection of antibodies in sera of Burkholderia pseudomallei-immunized goats - Mekaprateep M. (2014)
A modified, non-species dependent ELISA was performed to detect antibodies in sera of Burkholderia pseudomallei-immunized goats using protein G- or protein A-peroxidase conjugates. The rise of antibody titers during the immunization period exhibited corresponding results by modified ELISA comparison to conventional ELISA and the IHA. Regarding the increase of antibody levels from the pre-immunized baseline to the post-immunized status, the antibody titer detected by modified ELISA was higher than IHA but lower than conventional ELISA. Further efforts are needed to improve the modified ELISA for the diagnosis of melioidosis in animals. © 2010 Elsevier B.V.